PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DENGAN PEMBELAJARAN KONVENSIONAL PADA MATA PELAJARAN AKUNTANSI SISWA KELAS XI IPS SMA NEGERI 9 PADANG - Putri, Yuni; Wahyuni, Sri; Afriza, Rina (Pendidikan Ekonomi, 2013)
Abstract This research is motivated by the low results obtained studying accounting class XI IPS SMAN 9 Padang school year 2012/2013 . This study aims to look at differences in student learning outcomes using learning model Student Teams Achievement  Division  (  STAD  )  with  conventional  learning  in  class  XI  IPS SMAN 9 Padang .This type of research is experimental research . The population in this study were all students of class XI IPS SMAN 9 Padang listed in the school year2012/2013  which  consists  of  4  classes  .  Sampling  was  done  by  purposive sampling technique and was chosen as the experimental class is class XI IPS 1 and IPS 2 control class XI .Instrument used is the final test form a valid objective and reliabelnya =0.80 at 95 % confidence interval . Instrument used in this study is the achievement test . Form of test used is an objective form . Data analysis techniques used with the help of software SPSS version 16.0 .Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples . Results of experimental class learning with an average of 82.7 is higher than the control class average of 73 . While the results obtained from testing the hypothesis sig ( 000 ) < of alpha ( 0:05 ) . Because the sig < of alpha then H0 is rejected and H1 is accepted . So based on hypothesis test results , we can conclude that the difference There are Student Learning Outcomes Using cooperative learning model type Student Teams Achievement Division ( STAD With Conventional Learning Subjects Accounting Students In Class XI IPS SMAN 9 Padang . Keywords : cooperative learning Student Teams Achievement Division ( STAD )